Clown care in the clinical nursing of children: a meta-analysis and systematic review - Wang, Lina; Zhu, Jing; Chen, Ting (Frontiers in Pediatrics, 2024)
Background: Children treated in hospitals are often accompanied by high levels of anxiety and pain. The purpose of this meta-analysis was to analyze the effect of clown care in the clinical nursing on children and to provide ideas for clinical nursing of children. Methods: Two authors searched PubMed, Embase, Clinical trials, Cochrane Library, Web of Science, CINAHL, Scopus, China National Knowledge Infrastructure (CNKI), Weipu and Wanfang databases for randomized controlled trials (RCTs) on clown care for children until September 15, 2023. The quality of included RCTs was evaluated and the data were extracted by two researchers, and RevMan5.4 was used for meta-analysis. Results: 15 RCTs involving 2252 children were finally included in this meta-analysis. The results of meta-analysis indicated that clown care was beneficial to reduce the pain degree [SMD=-0.96, 95%CI (- 1.76,0.16)], anxiety degree [SMD=-0.81, 95%CI (- 1.16, -0.46)], crying time [SMD=-1.09, 95%CI (- 1.74, -0.44)] and caregivers’ anxiety level [SMD=-0.99, 95%CI (- 1.95, -0.03)] of children (all P<0.05). There were no significant publication biases in the synthesized outcomes (all P>0.05). Conclusions: Clown care is helpful to reduce children's pain, anxiety and crying time, and decrease the caregivers' anxiety level. More high-quality studies with larger sample size are warranted to further analyze the role of clown care in clinical practice.